Factors Affecting Consumers' Perception on Electronic Payment System (The Lumbini Journal of Business and Economics, 2021)
The recent growth and development of technologies has led to considerable improvement in internet technologies. Largely, electronic business services are fulfilling consumer’s requirements. Electronic payment (e-payment) systems are increasingly popular in Nepal, due to the widespread use of internet for shopping and banking services as well as COVID-19 have influence people in using e-payment channels. Nepal has established a different online payment platform with other online payment services to facilitate sending and/or receiving of services for individuals or corporations via electronic channels. This study has developed a conceptual model to examine the significant factors that influence consumers’ perception of e-payment in Nepal. The findings of a sample set of respondents (384) analyzed using multiple regression analysis indicate that benefit, ease of use, security and self-essence influence Nepal consumers’ perception of e-payment systems, while trust is not significantly associated with consumers’ perception of e-payment.